PERSEPSI STAKEHOLDERS TERHADAP KURIKULUM FAKULTAS SYARIAH DAN BISNIS IAIN MALIKUSSALEH - Safriadi Safriadi (deliberatif, 2017)
Abstract: This research is a field research by using descriptive evaluative method and philosophical normative approach to empirical data by considering answers from interviews both from alumni and graduate users (stakeholder). The results of this study reveal that the way to realize the curriculum within the Faculty of IAIN Malikussaleh Syari'ah in accordance with the needs of stakeholders is to conduct curriculum development. In general, Syari'ah curriculum is in accordance with the needs of the community, but there are some courses that do not support the work of alumni in the community. This requires reinforcement of the profession deepening courses, how to reproduce the lab in the college courses and add proficient in-depth profession required in accordance with the development of modern society. The relevance of the curriculum to the needs of the community can be seen in two ways covering the curriculum relevance in the Shari'ah Department to the Life skill of the work according to the educational background and the relevance of the course to the work required by the appropriate stakeholder of the educational background.